The perceived value of place brand ecosystems : An exploratory research on tourist preferences - Nordström, Martin (Luleå tekniska universitet, Industriell ekonomi, 2022)
In the pursuit of attracting more tourists in a market where competition is growing on a global scale, place branding has become increasingly more common. An underexplored alternative within the place branding literature is place brand ecosystems, and how they can create value for both the place brand itself as well as the tourists that travel there. This thesis aimed to research how a place brand ecosystem can be conceptualised as well as how tourists derive value from viewing a place brand as a place brand ecosystem. The conceptualisation of the place brand ecosystem was conducted through a literature review, leading up to the construction of a conceptual framework. The constructed framework showed that a place brand ecosystem could be conceptualised through interactions between stakeholders, place brand perception, and value co-creation. This framework also set the basis for an interview guide to understand tourist value perception of place brand ecosystems. The data collection was conducted through a set of semi-structured interviews consisting of 11 respondents holding a degree of interest of Arjeplog as a tourist destination. The results of the data collection showed that tourists saw value in functional attributes being more easily accessible to each other, meaning a place brand ecosystem where stakeholders co-operate will be able to construct their functional attributes more easily. The attributes themselves will differ between places, and the place brand ecosystem must identify their strengths and weaknesses among the stakeholders and adjust accordingly. Furthermore, the place brand ecosystem must manage the brand positioning in relation to the brand image, meaning they must meet the expectations they have set out to market, or the tourists would leave discontent as opposed to if they had travelled there without expectations.